A new species of Entomobrya Rondani, 1861 (Collembola, Entomobryidae, Entomobryinae) from Croatia with the redescription of Entomobrya margaretae Gruia, 1967 - Winkler, Daniel; Grujić, Nikola Z.; Fiera, Cristina (Zootaxa, 2023)
In the present paper, a new species of the genus Entomobrya is described from Croatia. E. silvicola sp. nov. has a unique colour pattern that distinguishes it from other Entomobrya species in Europe and worldwide. Besides the different colour pattern, there are notable differences in the dorsal macrochaetotaxy and other characters that distinguish the new species from the other Entomobrya sharing the same dorsal macrochaetotaxy formula of Abd II–III. Herein, we also provide the redescription of E. margaretae Gruia, 1967, based on topotypic specimens, of which a neotype was designated.